Fostering Discipline in Early Childhood through Religious Practices: A Study of an Islamic Kindergarten in Makassar - Naimah, Nadratan; Sahrir, Sultan; Rusmayadi, Rusmayadi; Amal, Azizah (GENIUS: Indonesian Journal of Early Childhood Education, 2024)
This study explores how structured and systematic approaches, integrated with religious practices, develop disciplined behavior in children at an Integrated Islamic Kindergarten in Makassar, Indonesia. Data were collected through observation, interviews, and documentation over two weeks using a phenomenological qualitative method. Key findings demonstrate that consistent routines, teacher examples, and positive reinforcement significantly enhance discipline, contributing to strong character formation in children. This research enriches the literature on early childhood education, particularly in integrating Islamic teachings into discipline strategies, and provides actionable insights for educators in similar contexts.